Climate Change Adaptation Assistance to a Number of Environmental Communities in Mataram City in Supporting NTB's Commitment to Net Zero Emission - Ismah Rustam; Sabilla, Kinanti Rizsa; Syaiful Anam (Prospect Publishing, 2023)
This community service activity is carried out to provide assistance to a number of environmental communities engaged in Mataram City regarding climate change issue. The education presented how the NTB Provincial Government responded in formulating regional policies departing from the UNFCCC International Forum. The NTB government as a sub-state actor managed to become a representative of provinces throughout Indonesia to attend the COP event in Glasgow, England. This brings many positive impacts to environmental-based development in the NTB region. For island provinces such as NTB, the impact of climate change is very much felt like the occurrence of droughts, weather changes, floods, and others so that in supporting Indonesia's commitment to realizing Net Zero Emission, the NTB government has compiled a clear roadmap to support this. NTB is directed at environmentally friendly based development which is reduced to four excellent programs, namely NTB Zero Waste or Clean NTB, Green NTB, New and Renewable Energy and Ecotourism. The implementation of the four programs is certainly not only feasible for my government but the role of the environmental community will be very supportive so that this community service activity is expected to bring contributions to realize NTB's commitment towards Net Zero Emission.